لتعزيز استيعاب تصريف الفعل المضارع لدى طلاب الصف الثاني في المدارس الابتدائية بمنطقة كوالا لانجات، ولاية سلانجور B.O.F.I.M فعالية استخدام استراتيجية: The Effectiveness of Using the B.O.F.I.M Strategy to Enhance Understanding of Present Tense Conjugation Among Second-Year Students in Primary Schools in the Kuala Langat Region, Selangor State - Mohamad Sharif, Fatin Nur Syafiqah (SIBAWAYH Arabic Language and Education, 2024)
تهدف هذه الدراسة إلى معالجة مشكلة الارتباك التي يواجهها الطلاب عند تعلم تصريف الفعل المضارع في اللغة العربية، حيث يعتبر تصريف الفعل المضارع من أكثر الجوانب اللغوية تعقيداً بالنسبة للطلاب، خاصةً فيما يتعلق بفهم وإضافة حروف المضارعة التي تشير إلى الجنس والعدد وتطابق الفعل مع الضمير المناسب. يترتب على هذه الصعوبات ضعف في أداء الطلاب وقدرتهم على حفظ التصريف بشكل دقيق. ومن هنا، تسعى الدراسة إلى تقييم فعالية استخدام ابتكار B.O.F.I.M  كأداة تعليمية مبتكرة لتسهيل فهم الطلاب لتصريف الفعل المضارع، لا سيما فيما يتعلق بتحديد حروف المضارعة المناسبة بناءً على الضمائر المختلفة. شملت الدراسة 37 طالبًا من معهد في كانجوغ دارت بولاية سلانجور، تم تقسيمهم إلى 22 طالبًا و15 طالبة. تم تقييم فعالية ابتكار  B.O.F.I.Mباستخدام الاختبارات القبلية والبعدية التي أجريت عبر الإنترنت، بالإضافة إلى الملاحظات الميدانية أثناء عملية التدريس. أظهرت النتائج أن الابتكار ساهم في تحسين قدرة الطلاب على فهم تصريف الفعل المضارع وحفظه بشكل أكثر سهولة وفعالية، وذلك من خلال تطبيق أساليب بصرية وغنائية تفاعلية تركز على تبسيط المفاهيم اللغوية. تساهم هذه الدراسة في تقديم أسلوب تعليمي مبتكر يعزز من أداء الطلاب في مادة اللغة العربية، ويعالج بشكل مباشر الصعوبات التي يواجهونها في تعلم تصريف الفعل المضارع، كما تفتح الباب أمام استخدام استراتيجيات تعليمية جديدة تعتمد على التفاعل والتحفيز.This study embarks on a journey to address the confusion faced by students when learning the conjugation of the present tense verb in Arabic, a linguistic aspect deemed highly complex for learners. This complexity arises particularly in understanding and applying the markers of mood that indicate gender and number, and aligning the verb correctly with the appropriate pronoun. These challenges result in poor student performance and their inability to memorize verb forms accurately. To navigate through these academic rapids, the study evaluates the effectiveness of the innovative educational tool B.O.F.I.M, designed to ease students' understanding of present tense conjugation, focusing especially on identifying the correct mood markers based on different pronouns. The study encompassed 37 students from one of the secondary school in Selangor, divided into 22 boys and 15 girls. The efficacy of B.O.F.I.M was assessed through pre and post-tests conducted online, along with field observations during the teaching process. The results illuminated that the innovation significantly improved students' abilities to understand and memorize the conjugation of the present tense verb more effortlessly and effectively. This was achieved by employing interactive visual and auditory methods that simplify linguistic concepts. This study contributes to presenting an innovative teaching style that not only enhances students' performance in the Arabic language but also directly addresses the difficulties they encounter in learning verb conjugation. Moreover, it opens doors to new educational strategies that rely on interaction and motivation, paving the way for a more engaging and effective learning environment.Keywords: Tasrif Fi’il Mudhori' (conjugation of present tense verb), game, B.O.F.I.M innovation.